New tropisms of porcine epidemic diarrhoea virus (PEDV) in pigs naturally coinfected by variants bearing large deletions in the spike (S) protein and PEDVs possessing an intact S protein. Issue 6 (3rd June 2020) - Van Diep, Nguyen; Choijookhuu, Narantsog; Fuke, Naoyuki; Myint, Ohnmar; Izzati, Uda Zahli; Suwanruengsri, Mathurot; Hishikawa, Yoshitaka; Yamaguchi, Ryoji
Abstract: We previously reported the coinfection of novel porcine epidemic diarrhoea virus (PEDV) variants bearing large deletions in the S protein and PEDVs possessing an intact S protein (S‐intact PEDV) in domestic pigs in Japan. The variants were frequently observed in pig farms with persistent or recurrent infection. To elucidate the role of the variants in persistent infections and their tropism properties, we genetically characterized and immunohistochemically detected PEDVs collected in primary and recurrent outbreaks in two persistently infected farms. Our results revealed coinfection of the PEDV variants bearing a 214‐amino acid deletion in the S protein and S‐intact PEDVs in the lungs of the naturally infected pigs. New tropisms of PEDV, including epithelial cells and submucosal glands of the airway tract, epithelial cells of the bile duct, and monocytes/macrophages were identified. The findings elucidate the mechanism of PEDV infection, epidemiology and pattern changes in the disease.